Innovative technology for large-scale photovoltaic consumption using reversible solid oxide cells - Mao, Hongtao; Nie, Dong; Chen, Xi; Cai, Yanan; Zhao, Jie; Zhang, Xuzheng; Yu, Haoyu; Ma, Wanli; Lv, Zepeng; Zhou, Jun (Frontiers in Energy Research, 2023)
It is inevitable that renewable energy consumption will increase as installed capacity continues to increase, primarily wind and photovoltaic power generation. Power to Gas (P2G) technology can store electrical energy in the form of chemical energy on a large scale. Reversible solid oxide cell (RSOC) has a very high conversion efficiency in both electrolytic gas production and fuel cell power generation compared with traditional electricity-to-gas devices. For the future integrated energy system, Reversible solid oxide cells are expected to play a significant role in integrating power generation and energy storage. This work proposes a new integrated energy system based on Reversible solid oxide cell for photovoltaic (PV) consumption. The Integrated Electricity-Gas System (IEGS) considers the two modes of electrolysis and power generation of Reversible solid oxide cell in the model. The model takes the minimum running cost as the objective function to linearize part of the model to generate a mixed integer linearization problem and solve it in GAMS. The case study shows that wind power is maximized, and the gas mixture can be transported in natural gas pipelines, improving the economics and stability of Integrated Electricity-Gas System. This work not only can reduce the operating cost of the system but also increase the high penetration of photovoltaic power generation. A quantitative assessment of the impact of hydrogen injection ratio and renewable energy penetration was also carried out.